Analisis Kerawanan Longsor dengan Metode Analytical Hierarchy Process (AHP) di Desa Kopi, Kecamatan Bulango Utara, Kabupaten Bone Bolango, Gorontalo - Mirdayanti Dachi; Sri Maryati; Noviar Akase (Mataram University, 2026)
Landslides are common natural disasters in Indonesia, particularly in areas with steep topography and high rainfall. Kopi Village, Bulango Utara District, Bone Bolango Regency, Indonesia, has experienced several landslide events and remains susceptible to future occurrences. This study aims to analyze landslide susceptibility in Kopi Village using the Analytical Hierarchy Process (AHP) integrated with Geographic Information Systems (GIS). The parameters used include slope, rainfall, land use, lithology, and distance from lineaments. The AHP results indicate that slope is the most influential parameter (35%), followed by rainfall (30%), land use (14%), lithology (13%), and distance from lineaments (8%), with a Consistency Ratio (CR) of 0.084. Landslide susceptibility mapping shows that the study area is dominated by the high susceptibility class, covering 3.10 km² (54.34%), followed by the moderate class at 2.05 km² (35.95%) and the low class at 0.55 km² (9.71%). These findings can serve as a basis for landslide mitigation and disaster risk reduction in Kopi Village.